OsBBX11 on qSTS4 links to salt tolerance at the seeding stage in Oryza sativa L. ssp. Japonica - Lei, Lei; Cao, Liangzi; Ding, Guohua; Zhou, Jinsong; Luo, Yu; Bai, Liangming; Xia, Tianshu; Chen, Lei; Wang, Jiangxu; Liu, Kai; Lei, Qingjun; Xie, Tingting; et al. (Frontiers in Plant Science, 2023)
Rice has been reported to be highly sensitive to salt stress at the seedling stage. However, the lack of target genes that can be used for improving salt tolerance has resulted in several saline soils unsuitable for cultivation and planting. To characterize new salt-tolerant genes, we used 1,002 F2:3 populations derived from Teng-Xi144 and Long-Dao19 crosses as the phenotypic source to systematically characterize seedlings’ survival days and ion concentration under salt stress. Utilizing QTL-seq resequencing technology and a high-density linkage map based on 4,326 SNP markers, we identified qSTS4 as a major QTL influencing seedling salt tolerance, which accounted for 33.14% of the phenotypic variation. Through functional annotation, variation detection and qRT-PCR analysis of genes within 46.9 Kb of qSTS4, it was revealed that there was one SNP in the promoter region of OsBBX11, which resulted in a significant response difference between the two parents to salt stress. Transgenic plants using knockout-based technology and demonstrated that Na+ and K+ in the roots of the functional-loss-type OsBBX11 were translocated largely to the leaves under 120 mmol/L NaCl compared with the wild-type, causing osbbx11 leaves to die after 12 days of salt stress due to an imbalance in osmotic pressure. In conclusion, this study identified OsBBX11 as a salt-tolerance gene, and one SNPs in the OsBBX11 promoter region can be used to identify its interacting transcription factors. This provides a theoretical basis for finding the molecular mechanism of OsBBX11 upstream and downstream regulation of salt tolerance and molecular design breeding in the future.